KEDUDUKAN DPD RI DALAM SISTEM TATA NEGARA PERSPEKTIF SIYASAH - SITI NURKHADIJAH; Zul Anwar AJim Harahap (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
The discussion of this paper is motivated by the contradiction of functions, roles and competencies of the DPD RI. The purpose of this research was to find out the position of the DPD in the Indonesian state system and to find out the views of the siyasa fiqh on the position of the DPD in the Indonesian constitutional system. The results of this research indicated that the position of the DPD RI in the Indonesian state system has limited position and authority. The position and competence of the RI DPD should be strengthened so that the performance of a DPD RI institution becomes better in regional autonomy. If the DPD RI has an unlimited position, it gives a special authority in building the region. The view of siyasa fiqh towards the position of the Republic of Indonesia Regional Representative Council in the Indonesian state system is inconsistent and inappropriate, because Ahlul al-Halli wa al-'Aqdi is a representative of the people who can give fatwa, while the DPD RI is an institution that has the authority limited